Masyarakat Maju dalam Peradaban Islam Perspektif Said Ramadhan al-Buthi - Elfira Hanum (Jurnal Al-Tatwir, 2023)
There have been many civilizations that have existed and developed throughout the world in human history, including Ancient Egyptian civilization, Ancient Greek civilization, Ancient Persian civilization, Ancient Chinese civilization, Ancient Indian civilization, Islamic civilization in the Middle East and North Africa, and so on. This research uses the library research method. In this research, the author searches for reference sources such as books, journals, and theses related to advanced civilizations in the perspective of Sa'id Ramadhan al-Buthi. The purpose of this research is to understand advanced civilizations in the perspective of Sa'id Ramadhan al-Buthi. Said Ramadhan Al-Buthi is a Muslim scholar who argues that a good civilization must be able to provide happiness and prosperity for humans as a whole and must be based on good moral and ethical principles as well as positive religious values. Al-Buthi's view of civilization also emphasizes the importance of moral and ethical values in creating a quality civilization, as well as the importance of the contribution of civilization to the progress of humanity and the well-being of society as a whole.